The Degree of Fear of Losing the Phone (Nomophobia) among Visually Impaired Jordanian University Students - Al-Momani, Islam Shukri Abdul Aziz; Al-Sharaa, Faisal Khalif; Anza, Abrar Youssef Abu; Khamis, Esra’ Mohammad Mustfa (Journal of Ecohumanism, 2024)
The study aimed to identify the degree of fear of losing the phone (Nomophobia) among students with visual impairment enrolled in Jordanian universities. In contrast, the study consisted of (300) male and female students with visual impairment enrolled in Jordanian public universities. To achieve the objectives of this study, the researchers used the nomophobia scale; the results showed that the prevalence of Nomophobia among Jordanian university students with visual impairment was high. The research found a substantial dependence on mobile phones, with an average score of 3.70, suggesting a high level of anxiety regarding the potential loss of phone connectivity. Anxiety feelings were recorded when people’s ability to communicate with loved ones was interrupted; the highest reported score was 4.40. When looking at gender, academic year, and degree, there were noticeable variances. The average Nomophobia score was 3.98 for females and 4.00 for males; the most significant levels were seen among first-year students. Students with visual impairments may be more or less dependent on mobile technology, depending on their level of education; students with a diploma or less had the most significant levels of Nomophobia (average score: 3.97).